Projection of the use of primary health care services in a greek primary health centre: a pilot study - Noula, Maria; Gesouli, Eftihia; Vobiris, G.; Raftopoulos, Vasilios (My University, 2007)
Primary health care services are the cornerstone of many health care systems in Europe.The systematic analysis of annual consultation rates in the primary care centres is important for the evaluation of the performance and the adequacy of care provided.
Keywords: Health care centre; Primary health care; Demand; Use of care services